Preliminary Results on Prompt \(Ξ^+/Ξ^-\) Production ratio in \(pp\) Collisions at \(s = 7 TeV\) - Chung, Nguyen Mau; Dung, Nguyen Thi; Tam, Tran Minh (Communications in Physics, 2011)
The ratio of prompt \(Ξ^+/Ξ^-\) production has been investigated from a limitedsample of data registered by the LHCb experiment at the CERN Large Hadron Colliderin 2010. This ratio has been determined in the rapidity region \(1.9 ≤ y ≤ 4.9\) covered bythe LHCb detector. The determination of anti-hyperons to hyperons production ratio willallow to study the transport of baryon number from pp collisions to final state hadrons andto constrain and tune Monte Carlo models